2023
DOI: 10.21927/ijnd.2023.11(1).1-10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 fatty acids and vitamin E supplementation on lipid profiles and inflammatory markers in hemodialysis patients: A systematic review of current literature

Abstract: <p align="center"><strong>ABSTRAK </strong></p><p><strong><em>Latar Belakang: </em></strong><em>Kebutuhan terapi hemodialisis (HD) masih terus berkembang. Di Indonesia, HD mewakili 82% dari pelayanan cuci darah di Puskesmas Indonesia.</em><strong><em> </em></strong><em>Namun, HD menyebabkan peningkatan penanda inflamasi serta perubahan profil lipid. Kombinasi vitamin E dan asam lemak omega-3 dapat membantu mengurang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…A recent meta-analysis, similar to our study, concluded that omega-3 and vitamin E co-supplementation can improve lipid profiles, such as TG, TC, LDL and HDL (Meliana et al. , 2023).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent meta-analysis, similar to our study, concluded that omega-3 and vitamin E co-supplementation can improve lipid profiles, such as TG, TC, LDL and HDL (Meliana et al. , 2023).…”
Section: Discussionsupporting
confidence: 86%
“…A recent meta-analysis, similar to our study, concluded that omega-3 and vitamin E cosupplementation can improve lipid profiles, such as TG, TC, LDL and HDL (Meliana et al, 2023). Many of the previous meta-analyses of RCTs could not find adequate evidence for a beneficial effect of vitamin D supplementation on lipid profile (Challoumas, 2014).…”
Section: Effects Of Vitamin D and Omega-3supporting
confidence: 51%